Application of 3D Scanning Technology for Evaluation of Virtual Model of Gun Geometry - Bartosz FIKUS; Robert PASZKOWSKI; Paweł PŁATEK (Problemy Mechatroniki, 2018)
The paper presents the results of reconstruction of selected gun elements with application of 3D scanning technology. Algorithm of under investigation process, the way of preparing object for scanning and measuring process were also presented. This article discusses also data acquisition of clouds of points and methods of some activities with measured geometry data (i.e. solving some imperfections caused by the preparation or by the measurement process). Geometry was remeshed by the creating a new mesh of polygons to unify shapes defined after previous steps. On the basis of cloud of points measurements, the solid geometry of the whole object was prepared. The effect proved satisfactory accuracy of the estimated parts’ characteristics and allowed for recommendation of the mentioned approach in the described process.